On the contribution of sunspots to the observed frequency shifts of solar acoustic modes. Issue 1 (8th June 2016) - Santos, A. R. G.; Cunha, M. S.; Avelino, P. P.; Chaplin, W. J.; Campante, T. L.
Abstract: Activity-related variations in the solar oscillation properties have been known for 30 years. However, the relative importance of the different contributions to the observed variations is not yet fully understood. Our goal is to estimate the relative contribution from sunspots to the observed activity-related variations in the frequencies of the acoustic modes. We use a variational principle to relate the phase differences induced by sunspots on the acoustic waves to the corresponding changes in the frequencies of the global acoustic oscillations. From the sunspot properties (area and latitude as a function of time), we are able to estimate the spot-induced frequency shifts. These are then combined with a smooth frequency shift component, associated with long-term solar-cycle variations, and the results compared with the frequency shifts derived from the Global Oscillation Network Group data. The result of this comparison is consistent with a sunspot contribution to the observed frequency shifts of roughly 30 per cent, with the remaining 70 per cent resulting mostly from a global, non-stochastic variation, possibly related to the changes in the overall magnetic field. Moreover, analysis of the residuals obtained after the subtraction of the model frequency shifts from the observations indicates the presence of a 1.5-yr periodicity in the data in phase with the quasi-biennial variations reported in the literature.